Temperature is a regulator of leaf production in the family Dipterocarpaceae of equatorial Southeast Asia. Issue 11 (14th November 2020) - Kobayashi, Masaki J.; Ng, Kevin Kit Siong; Lee, Soon Leong; Muhammad, Norwati; Tani, Naoki
Abstract : Premise: Leaf phenology is an essential developmental process in trees and an important component in understanding climate change. However, little is known about the regulation of leaf phenology in tropical trees. Methods: To understand the regulation by temperature of leaf phenology in tropical trees, we performed daily observations of leaf production under rainfall‐independent conditions using saplings of Shorea leprosula and Neobalanocarpus heimii, both species of Dipterocarpaceae, a dominant tree family of Southeast Asia. We analyzed the time‐series data obtained using empirical dynamic modeling (EDM) and conducted growth chamber experiments. Results: Leaf production by dipterocarps fluctuated in the absence of fluctuation in rainfall, and the peaks of leaf production were more frequent than those of day length, suggesting that leaf production cannot be fully explained by these environmental factors, although they have been proposed as regulators of leaf phenology in dipterocarps. Instead, EDM suggested a causal relationship between temperature and leaf production in dipterocarps. Leaf production by N. heimii saplings in chambers significantly increased when temperature was increased after long‐term low‐temperature treatment. This increase in leaf production was observed even when only nighttime temperature was elevated, suggesting that the effect of temperature on development is not mediated by photosynthesis. Conclusions: Because seasonal variation in temperature in the tropics is small, effects on leaf phenology have been overlooked. However, our results suggest that temperature is a regulator of leaf phenology in dipterocarps. This information will contribute to better understanding of the effects of climate change in the tropics.